Hippocrates Now The 'Father of Medicine' in the Internet Age - King, Helen (Bloomsbury Academic, 2020)
This book challenges widespread assumptions about Hippocrates (and, in the process, about ancient Greek medicine) and will also explore the creation of modern myths about the ancient world. Through the lens of reception studies Helen King considers what 'Hippocrates' means today. He features powerfully in our assumptions about ancient medicine, and our beliefs about what medicine - and the physician himself - should be. In ethics, as well as in actual treatments recommended by both orthodox and alternative medicine, 'Hippocrates' still features as a model to be emulated. Why do we continue to use him in this way, and how are new myths constructed around his name? And what can this tell us about popular engagements with the classical world today?